Urinary Tract Infection in Nephrotic Syndrome: A Hospital Based Cross-Sectional Study - Barua, Tanuka; Sultana, Razia; Babul, Fazal Karim; Iqbal, Shahed; Sharma, Jhulan Das; Dutta, Pradip Kumar (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Urinary Tract Infection (UTI) is a common infection in nephrotic syndrome and have a propensity for long term renal damage. It may be an important cause of poor steroid response. The objective is to study the frequency and etiological organisms of urinary tract infection in idiopathic nephrotic syndrome children. Methods: This Comparative cross-sectional study was conducted in the Pediatric ward of Chittagong Medical College Hospital, Chittagong from 01.01.2009 to 31.12.2009. 52 nephrotic syndrome children diagnosed by serum albumin, serum cholesterol and 24 hours total urinary protein or protein creatinin index were included. After elaborate clinical evaluation, urine for R/M/E and C/S was done in all patients. Data regarding pyuria, hematuria, etiological organisms were analyzed by statistical method. Results: UTI was found in 30.8% nephrotic children and in majority cases (68.8%) they were asymptomatic. Male female ratio among UTI patients was 1:1. Mean serum cholesterol in nephrotic syndrome with UTI was higher than that of children without UTI (418.94 mg/dl vs 352.03 mg/dl, p value < 0.05).Pyuria had poor association with definite UTI (p value > 0.05). E-coli was the commonest organism isolated in urine culture followed by klebsiella. Conclusion: UTI is one of the most common infections in nephrotic syndrome and may be asymptomatic. It should be screened in every nephrotic child routinely. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 41-44